Hubungan pengetahuan dan sikap terhadap perilaku merokok pada remaja - Suharti, Sri; Marliyana, Marliyana (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Smoking is one of the activities carried out by an individual from children to adults, it is possible for individuals who have previously smoked to smoke again, or for individuals who have never smoked to be interested in trying it. The Ministry of Health of the Republic of Indonesia released the results of a global survey of tobacco use in adults (Global Adult Tobacco Survey-GATS) conducted in 2011 stating that over the past 10 years there has been a significant increase in the number of adult smokers increasing by 8.8 million people, from 60.3 million in 2011 to 69.1 million smokers in 2021. Purpose: To determine the relationship between knowledge and attitudes towards smoking behavior in adolescents. Method: Cross-sectional research design with emphasis on the time of data measurement/observation is only done once using the Chi square test. The sample used by researchers was 47 respondents. Data analysis used univariate and bivariate analysis using the chi square test. Results: Most respondents have good knowledge 70.2%, negative attitude 59.6% and negative behavior 61.7%. The results of the Chi square test showed that there was a significant relationship between knowledge and smoking behavior in adolescents p = 0.008 (p <0.05) and there was a significant relationship between attitudes and smoking behavior in adolescents p=0.004 (p <0.05). Conclusion: There is a significant relationship between knowledge and attitudes towards smoking behavior in adolescents. Keyword: Attitude; Knowledge; Smoking Behavior in Adolescents. Pendahuluan: Merokok adalah salah satu kegiatan yang dilakukan oleh seorang individu mulai dari anak-anak hingga dewasa, tidak menutup kemungkinan individu yang sebelumnya sudah merokok kemudian merokok kembali, ataupun bagi individu yang belum pernah merokok menjadi tertarik untuk mencobanya. Kementerian Kesehatan Republik Indonesia merilis hasil survei global penggunaan tembakau pada usia dewasa (Global Adult Tobacco Survey-GATS) yang dilaksanakan pada tahun 2011 menyatakan selama kurun waktu 10 tahun terakhir terjadi peningkatan signifikan jumlah perokok dewasa meningkat sebanyak 8.8 juta orang, dari 60.3 juta tahun 2011 menjadi 69.1 juta orang perokok tahun 2021. Tujuan: Untuk mengetahui hubungan pengetahuan dan sikap terhadap perilaku merokok pada remaja. Metode: Desain penelitian Cross sectional dengan menekankan waktu pengukuran/observasi data hanya dilakukan satu kali dengan menggunakan uji Chi square. Sampel yang digunakan peneliti sebanyak 47 responden. Analisis data menggunakan analisis univariat dan bivariat menggunakan uji chi square. Hasil: Sebagian besar responden memiliki pengetahuan baik 70.2%, sikap negatif 59.6% dan perilaku negatif 61.7%. Hasil uji Chi square menunjukan terdapat hubungan yang bermakna antara pengetahuan terhadap perilaku merokok pada remaja p=0.008(p<0.05) dan terdapat hubungan yang bermakna antara sikap terhadap perilaku merokok pada remaja p=0.004(p<0.05). Simpulan: Terdapat hubungan yang bermakna antara pengetahuan dan sikap terhadap perilaku merokok pada remaja. Kata Kunci: Pengetahuan; Sikap; Perilaku Merokok pada Remaja.